Control of strong-field ionization with two-color laser pulses. (August 2015) - Camus, N; Fechner, L; Arbó, D G; Lemell, C; Nagele, S; Ullrich, J; Pfeifer, T; López, S D; Burgdörfer, J; Moshammer, R
Synopsis: Experimental results and theoretical analysis of the ionization process of argon atoms interacting with linearly polarized two-color fields (λ1 = 800 nm, λ2 = 400 nm ) are presented. We observe complex asymmetry patterns in the measured three-dimensional momentum distributions.